“THROUGH THE LANGUAGE A CHILD’S CONSCIOUSNESS IS REVEALED …”: CORRELATION BETWEEN VERBAL AND “OBJECTIVE” CODES IN CHILDREN’S WORLDVIEWS (Филологический класс, 2018)
The article characterizes the formation peculiarities of a child’s language consciousness in preschool ontogeny. This period is the main one for the development of language creativity. The article develops the idea of F. Buslaev about the role of the communicative and nominative competences in mastering the “objective” (extralinguistic reality) and “verbal” (language conceptualization of the world) language codes. In the given key, the researcher analyzes the mechanisms of linguo-creative thinking, which manifests itself in children's reflection on the form and content of linguistic signs at the stage of self-mastering the language. Factors that motivate children for creativity are: the desire to compress the meaning in a single word; to follow the “law” of language symmetry; to fill in the nominative gaps; to clarify the motivation of words and phrases. Particular attention is paid to the ability of children to understand and simulate the game code (during the assimilation of the usual metaphorical analogy in the genre of the brainteaser). The analysis is in complete agreement with the statement of F. Buslaev about the prohibition of formal language training, which destroys the “original” sense of the language in a child. As a promising field, the article postulates the need for introduction of special verbal creativity trainings in the learning process.